Factors Influencing the Cervical Cancer Screening uptake among Medical Lecturers at Faculty of Medicine Universitas Padjadjaran - Sri Yusnita Irda Sari; Phavithra Rathakirushnan; Edwin Armawan (Althea Medical Journal, 2019)
Background: Cancer is the leading cause of death worldwide. In Indonesia, cervical cancer is one of the most occurring types of cancer. It is acknowledged that early screening can prevent cervical cancer. This study aimed to explore what factors influenced the screening uptake and to correlate characteristics, perceived susceptibility, and self-efficacy of Pap smear uptake among medical faculty lecturers.Methods: This was a cross-sectional analytical study conducted among female lecturers in the Faculty of Medicine, Universitas Padjadjaran from October to November 2013. The questionnaire was used to collect data using a purposive sampling method. Data collected were tabulated into frequency and percentage and the correlation was performed using Pearson chi-square. Results: From a total of 79 respondents who participated, only 55.7% of medical lecturers had ever taken Pap smear. Reasons for not taking Pap smear were time (77.1%) and the perception of not being at risk (22.9%). However, most of the respondents (84.8%) were willing to have a screening test for cervical cancer routinely. There was a significant correlation between age (p=0.001), level of education (p=0.003) and duration of marriage (p=0.001) with the uptake of Pap smear.Conclusions: The factors that are influencing the uptake of screening are not having the time to take the test and the perception of not being at risk of the disease. There is a correlation between age, level of education and duration of marriage with screening uptake. Awareness of the importance of screening should also be promoted among female doctors.